Enantioselective hydrogen atom relay via non-covalent catalyst assembly - Navadheer Yalamanchili; Jules Hugo Alexandre; Robert L. Anderson; Giuseppe Zuccarello (Nature, 2026)
Abstract Most biological functions are regulated by chiral molecules 1 that contain at least one tertiary stereogenic carbon, that is, a carbon with one C( sp 3 )–H bond. Hydrogen atom transfer (HAT) 2 is a straightforward strategy that can be used to either edit 3 or introduce tertiary stereocentres in multiple synthetically useful transformations 4 , especially when coupled with photoredox catalysis 5,6 . However, traditional de novo design of chiral HAT catalysts that provide sufficient enantiocontrol over short-lived open-shell intermediates 7 has represented a major hurdle in the development of enantioselective HAT reactions. Here we describe a distinct approach in which chiral HAT catalysts are obtained in situ by non-covalent self-assembly of privileged chiral phosphoric acids and commercial 2-mercaptopyridines. The phosphoric acid serves as a modular interchangeable chiral element that renders the achiral thiol effectively chiral, thereby allowing access to a previously inaccessible combinatorial space of chiral HAT catalysts. This platform enabled the photochemical deracemization of 2-aryl pyrrolidines, which are prevalent scaffolds in active pharmaceutical ingredients. Optical enrichment occurs by means of enantioselective hydrogen atom relay, in which a single chiral assembly orchestrates hydrogen atom abstraction and delivery. This conceptual approach of relaying chiral information through non-covalent assembly paves the way for discovery of numerous asymmetric radical transformations.